Balancing the economy: The hand of government or the invisible hand? - J. R. Shackleton; Diego Zuluaga (Institute of Economic Affairs (IEA), 2016)
Despite its considerable strengths, the UK economy is seen as having a number of problems, in particular productivity which lags behind some competitors, low levels of investment and persistent regional disparities. Following the referendum decision to leave the EU, there is wide interest in developing a new industrial strategy. The UK has a growing comparative advantage in services which the government should not attempt to frustrate by favouring manufacturing. The past record of industrial policy in the UK is a catalogue of waste and ineffectiveness. By the end of the 1970s it was widely accepted that the strategy of attempting to pick winners and promoting national champions was fundamentally flawed. While political pressures mean that the revival of interest in industrial strategy is understandable, it is not clear that the sectorally-based policies being suggested are fundamentally different from those proposed in the past. Governments are still likely to be tempted to intervene for narrowly political motives and it is still assumed that governments possess insights which the private sector is denied. The UK's economy and its population would be better supported by a revival of 'horizontal' rather than 'sectoral' strategy, concentrating on boosting competition, relaxing planning controls, liberalising energy, deregulating markets and promoting tax reform. The government should also eschew protectionism and excessive restrictions on migration.
Keywords: L51; L52; L60; L70; L78; E62; L51; L52; L60; L70; L78; E62; 330